Analisis Penerapan Model Pembelajaran Team Games Tournament (TGT) dalam Peningkatan Minat Belajar Mata Pelajaran PPKn - Ria Yuni Lestari; Hj. Tati Rohmayati; Syifa Nandiny; Meidha Zulva Fadhila; Azzalfa Alifah Rizkya (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The teacher's accuracy in arranging learning activities really determines the quality of the learning process and outcomes. The current reality shows that the majority of teachers still use learning models that apply the old teacher-centered learning paradigm. This makes students less motivated in the learning process. Teachers are required to have high ability and creativity in planning citizenship learning activities. The aim of this research is to increase the learning interest of class VII students at SMPN 7 Serang in the subject of PPKn (Pancasila and Citizenship Education). The research method uses a qualitative descriptive approach with data collection through observation, interviews, documentation and literacy. The results of the research show an increase in interest in learning by using the cooperative learning model, namely the Team Games Tournament. The use of the cooperative learning model is applied as a varied model, especially in PPKn subjects and it can be concluded that students' learning interest in participating in PPKn learning is getting better and there is an increase.